2018
DOI: 10.1177/2309499018802504
|View full text |Cite
|
Sign up to set email alerts
|

A three-dimensional virtual morphometry study of the sigmoid notch of the distal radius

Abstract: Our primary objectives were to create a reliable, noninvasive method for three-dimensional morphometry of deep bony parameters within the sigmoid notch of the distal radius, to identify its morphological patterns, and to identify any significant variation between the left and the right wrists. Our secondary objectives were to obtain morphometric values that could represent our population and to identify any possible ethnic variations. Methods: Computed tomography scans of 102 wrists from 51 healthy individuals… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
8
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(8 citation statements)
references
References 13 publications
0
8
0
Order By: Relevance
“…The sigmoid notch is no exception, and the present MRI study confirms the four main morphology types originally described by Tolat et al 7 In their cadaver study, the most represented morphologies were type A (42%) and type C (30%), with type B and type D each representing 14% of the wrists. In a study on 102 wrists, Shivdas et al 12 found a majority of type D (52%), and some type C (26.4%) and type B (21.6%) variants, but they did not identify any type A (flat type). In our study, the most represented morphology was type C (60%), followed by type B (30%); types D and A were the least represented (6 and 4%, respectively).…”
Section: Discussionmentioning
confidence: 93%
See 1 more Smart Citation
“…The sigmoid notch is no exception, and the present MRI study confirms the four main morphology types originally described by Tolat et al 7 In their cadaver study, the most represented morphologies were type A (42%) and type C (30%), with type B and type D each representing 14% of the wrists. In a study on 102 wrists, Shivdas et al 12 found a majority of type D (52%), and some type C (26.4%) and type B (21.6%) variants, but they did not identify any type A (flat type). In our study, the most represented morphology was type C (60%), followed by type B (30%); types D and A were the least represented (6 and 4%, respectively).…”
Section: Discussionmentioning
confidence: 93%
“…This discrepancy may be due to the limited number of wrists in our study, the study of healthy subjects rather than cadavers, and measurements completed using MRI rather than CT scans. 12 Tolat et al 7 based their descriptions on visual observation of midcoronal sections, lacking the defined elements of MRI analysis. Furthermore, compared to the cadaveric study of Tolat, the rest are based on biaxial imaging data.…”
Section: Discussionmentioning
confidence: 99%
“…The principal axes of the wrist on axial CT sections are used as a reference in studies for following conditions: the distal radius anatomy, [1,4,8,15] rotational malalignment due to distal radius or shaft fractures, [7,9,16] anatomic and kinematic studies of the carpal region, [5,6,10] and DRUJ anatomy. [5,11,12,[17][18][19] Several anatomical locations have been used as principal axis of the distal radius in the past, including, the central axis, [4,[7][8][9]11,12,16] volar cortical axis at metaphyseal level, [5,8,9] and sigmoid notch axis. [5] In the current study, a series of angular measurements based on axial CT images provided improved data for evaluating radiographic anatomy of the wrist.…”
Section: Discussionmentioning
confidence: 99%
“…The sigmoid notch version angle is a fundamental axial parameter of the distal radius, [5,11,12,[17][18][19] This angle was used as a reference for kinematic studies of the DRUJ [5] and associated with some clinical conditions including triangular fibrocartilage tear [19] and DRUJ instability. [11,19] Jung et al [19] found an association between the DRUJ instability and the flat-face type of sigmoid notch described by Tolat et al [21] A flat-faced sigmoid notch inherently has a lower version angle, [19] and can be reconstructed with osteoplasty in case of instability.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation